(untitled) (Ustozlar uchun, 2025)
This article highlights the importance of teaching English to school-age and primary school children through English nursery rhymes. Research and observations have shown that the use of nursery rhymes as a pedagogical tool in education has a positive influence on young learners’ ability to acquire a second language easily and effectively.